THE INFLUENCE OF READING INTEREST ON STUDENTS’ DESCRIPTIVE WRITING SKILL AT VOCATIONAL SCHOOLS IN BOGOR - Octafia, Yani (Jurnal Ilmiah Humanika, 2020)
This study aims to determine and analyze the influence of reading interest on descriptive writing skill. The population observed in this study was tenth grade students of vocational schools in Bogor. In the academic year 2014/2015. Therefore, this research showed that reading interest positively influenced on students’ descriptive writing skill. The researcher conducted surveys, observations, and data collection related to, reading interest and descriptive writing skill on students in vocational school in Bogor. The population was 374 students. The sample of this study were 60. The data of this research in the form of questionnaire consists of 30 items about. The sample is obtained through a simple random sample, the researcher combines respondents in the population so that they will be measured in the same number. this research has 2 variables which divided into 1 independent variable (reading interest) and 1 dependent variable (descriptive writing skill). Data collection is done through questionnaire tests and written tests for all variables. Data acquisition was then analyzed using correlation techniques and multiple regression. before conducting a regression test, the analysis requirements test must be achieved first, such as the normality test and linearity test. The result of this study is that there is a significant effect on reading interest on the ability to write descriptive essays. this is proven by t0 = 4.438 and Sig. 0.000 < 0.05. this shows that descriptive writing skill is very mastered or influenced by reading interest they have.